Information and Society - Kurt, Ünal (Information World, 2025)
This study aims to analyze the book titled “Information and Society” written by Michael Buckland. The book consists of nine chapters, appendices-a/b, section for curious readers, glossary, references, and index. The chapters can be categorized into three sections. The first three chapters provide an introductory overview of the content, examining the historical development and necessity of the document concept, as well as its physical, cognitive, and social dimensions. The following three chapters discuss the importance of organizing big data, the effects of the information explosion, the functioning of processes in the electronic environment, the necessity of metadata, fundamental challenges in naming, and strategies to overcome them. The final three chapters focus on the systematic aspects of the search process, measurement methods used, efficiency calculations, and the relevance concept, which is the cornerstone of the field’s major debate on the quantity-quality problem. Each chapter includes a summary at the end, ensuring coherence between sections. The author presents the subject in a way that can be understood by a broad audience, concretizing abstract terminology through metaphors, while reinforcing conceptual and definitional explanations by referencing various authors and thinkers. As a general summary of Undergraduate level education in Turkey, this book is surely a guiding resource, especially for undergraduate students and other people who are interested in the field.
Keywords: Communication and society; documentation; information science; information society